Cancer pain - Paice, Judith (Henry Stewart Talks, 2021)
Trends in cancer pain, Etiology of cancer pain, Cancer survivors, Problems faced by cancer survivors who have persistent pain, Tumor and treatment related pain, Chronic pain syndromes associated with cancer treatment, Guidelines for treating cancer survivors who experience persistent pain, Challenges in managing pain associated with malignancies